Composition, Age, and Origin of Ordovician-Devonian Tanjianshan granitoids in the North Qaidam Orogenic Belt of northern Tibet: Implications for Tectonic Evolution. Issue 1 (2nd January 2023) - Xu, Chenghan; Sun, Fengyue; Fan, Xingzhu; Yu, Lu; Yang, Depeng; Bakht, Shahzad; Wu, Dongqian
ABSTRACT: The North Qaidam Orogenic Belt (NQOB) is characterized by widespread Palaeozoic magmatism and high to ultrahigh-pressure metamorphism that provides important information regarding the continental crust growth and tectonic evolution in the North Qaidam. Our work focuses on the geology, geochronology, whole-rock geochemistry, and Sr–Nd isotopy of granitoids in the Tanjianshan area in the northern NQOB. The results indicate that the 486–469 Ma adakitic and TTG-like granitoids originated from the partial melting of Middle–Late Mesoproterozoic lower crustal materials with the addition of juvenile mafic lower crust at high pressures under an active continental margin setting. The 396–392 Ma I-type granitoids originated from the partial melting of juvenile crustal materials with the addition of ancient crustal component in a post-collisional setting. Geochronological studies show that there are significant regional differences in magmatism between the northern and rest parts of the NQOB. In the northern part, extensive and prolonged magmatism was widespread during oceanic subduction (~526–460 Ma) and post-collisional extension (~420–350 Ma) but magmatism in the stage of orogenic collision was absent. The Early Palaeozoic adakitic magmatism suggest a significant continental crustal reworking in a subduction zone during 486–469 Ma along the NQOB. The initial oceanic subduction may have occurred prior to ca. 526 Ma. An intense and multiple-stage extension developed at ~420–350 Ma in the northern part of the NQOB following the orogenic collapse. Lithospheric delamination and subsequent mafic magma underplating may be the main geodynamic mechanism resulting in the uprooting of the continental crust and ore mineralization in response.